Primary prevention of colorectal cancer with low-dose aspirin in combination with endoscopy: a cost-effectiveness analysis. Issue 8 (13th October 2011) - Hassan, Cesare; Rex, Douglas K; Cooper, Gregory S; Zullo, Angelo; Launois, Robert; Benamouzig, Robert
Abstract : Objective: Low-dose aspirin reduces colorectal cancer (CRC) incidence and mortality. Recently, the aspirin effect has been shown to occur primarily in the proximal colon. Colonoscopy has been either less effective or ineffective in the proximal compared to the distal colon. The authors assessed the cost-effectiveness of adding low-dose aspirin to a simulated screening with colonoscopy or sigmoidoscopy. Design: A Markov model comparing the strategies of 10-year colonoscopy or sigmoidoscopy screening and the combination of either of the two with low-dose aspirin in 100 000 subjects aged 50 years until death was constructed. Proximal and distal CRC prevention rates with endoscopy or aspirin were extracted from the literature. Screening and aspirin prevention were simulated to stop at 80 years. The cost of aspirin and aspirin-related complications, as well as aspirin-related mortality, was included. Incremental cost-effectiveness ratios between the different strategies were calculated. Sensitivity and probabilistic analyses were also performed. Results: The addition of low-dose aspirin to colonoscopy and sigmoidoscopy screening increased the CRC death prevention rate from 68% and 39% to 81% and 69%, respectively. Lifetime aspirin-related mortality appeared to be 0.1%. Because of the substantial reduction in CRC care, the addition of aspirin to colonoscopy and sigmoidoscopy screening was cost-effective (incremental cost-effectiveness ratio: US$5413 per life-year saved) and cost saving (US$278 per person), respectively. When the proximal CRC prevention rate with colonoscopy was increased 56% to 73% from the baseline, the addition of aspirin was no longer cost-effective. The addition of aspirin to colonoscopy and sigmoidoscopy was a cost-effective strategy in 52% and 94% of the scenarios at probabilistic analysis. Conclusions: When assuming a suboptimal efficacy of endoscopy in preventing CRC, the addition of low-dose aspirin may be an effective and cost-effective strategy, mainly because of its high efficacy in preventing proximal CRC.